Authentication of geographic origin and production method of mullet (Mugil cephalus) roe using HRMS-based small-molecule fingerprinting - Yuchieh Tseng; Chia-Hui Wang; Yi-Chieh Lee; Chun-Yu Wang; Keng-Jui Lin; Jia-Zhen Yang; Yutong Chen (Food Control, 2027)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

First record of Brachyphyllum (Cheirolepidiaceae) from the Lower Jurassic of the Ordos Basin, China: Paleogeographic and paleoclimatic implications linked to T-OAE - Chao-Hui Wei; Yun-Feng Li; Chang-Lu Zhang; Xiao Tan; Fei Liang; Chun-Lin Sun; Tao Li; Yu-Ling Na (Review of Palaeobotany and Palynology, 2026)

Rehabilitation and seismic resilience of prestressed precast frames using replaceable steel buckling-restrained rods - Zhao-Hui Gong; Hai-Bo Fang; Man Xu; Jin Zhang; Chun-Lin Wang (Engineering Structures, 2026)

The progressive formation process of the tectono-metamorphic mélange belt: An example from the Mogutai massif, Dunhuang Orogenic Belt, Northwest China - Yichao Chen; Xue-Li Jia; Qian W.L. Zhang; Zhen M.G. Li; Hui C.G. Zhang; Hao Wang; Wenjiao Xiao; Yan-Lin Zhao; Haiquan Tang; Chang-Ming Lu; Chun-Ming Wu (Journal of Structural Geology, 2026)

Biochar-based cathodes for bioelectro-Fenton systems: Design strategies, electrocatalytic mechanisms, and environmental applications - Shu-Hui Liu; Chung-Yen Yeh; Wei-Tzu Huang; Yi-Chun Yu; Chi-Wen Lin (Journal of Environmental Chemical Engineering, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Metamorphic evolution and geochronology of garnet amphibolite, the Dongbatu tectonic-metamorphic mélange, eastern middle Paleozoic Dunhuang Orogenic Belt, northwest China - Xue-Li Jia; Yichao Chen; Yan-Lin Zhao; Zhen M.G. Li; Hui C.G. Zhang; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

Purification, Identification, and Functional Validation of Anti-Inflammatory Peptides from Protein Hydrolysates of Asian Seabass, Lates Calcarifer by-Product - Hui-Chen Lin; Chung-Chih Tseng; Jia-Yu Lu; Hua-Yi Liang; Chun-Hung Liu (Marine Biotechnology, 2026)

Monitoring photochemical reactions catalyzed by nano-titanium dioxide using electrospray laser desorption ionization mass spectrometry - Min-Zong Huang; Hsin-Hui Liang; Chi-Yang Lee; Shu-Yao Lin; Chun-Mei Wu; Jentaie Shiea (Analytica Chimica Acta, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Diverse metamorphic P‒T‒t paths of the Mogutai tectono-metamorphic mélange, eastern Paleozoic Dunhuang Orogenic Belt, northwestern China - Yan-Lin Zhao; Yichao Chen; Xue-Li Jia; Hui C.G. Zhang; Zhen M.G. Li; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Multi-source remote sensing for spatial mapping of salt-affected agricultural soils in Taiwan - Nguyen-Thanh Son; Chein-Hui Syu; Chi-Farn Chen; Cheng-Ru Chen; Huan-Sheng Lin; Yi-Ting Zhang; Tsang-Sen Liu; Chun-Chien Yen (Applied Geomatics, 2026)

Non-targeted screening of alprazolam and flualprazolam metabolites in in vitro metabolism of different species by high-resolution mass spectrometry - Jinxia Dai; Hui Lin; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Journal of Hazardous Materials, 2026)

Interpretable multi-task dual-attention model for forecasting heating load and supply water temperature in district heating systems - Yingfeng Lin; Chun-E Huang; Chunwang Li; Hui Wang; Chuanzhao Zhang (Energy and Buildings, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Correction to: Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2026)

Dexmedetomidine Mitigates Sevoflurane-Induced Neurodevelopmental Effects in Paediatric Anaesthesia: A Meta-Analysis and Preclinical Study - Hsuan-Chih Lao; Chia-Wei Huang; Ssu-Han Wang; Yen-Lin Su; Chien-Hui Chang; Cheng-Yen Liao; Jen-Chieh Wu; Ying-Chun Lin; Jin-Wu Tsai (Journal of Neuroimmune Pharmacology, 2026)
Sevoflurane (Sevo) anaesthesia in children is linked to an increased incidence of postoperative emergence agitation (EA) and potential neurotoxicity in developing brains. However, the specific risks of subanaesthetic foetal or neonatal exposure to Sevo remain unclear. This study evaluates the safety and efficacy of combining dexmedetomidine (Dex) with Sevo to manage EA in paediatric anaesthesia. A systematic review and meta-analysis of randomized controlled clinical trials involving children under 8 years old revealed that Dex significantly reduces EA incidence when administered via intravenous, perineural, and intranasal routes. Using in utero electroporation, we found that pregnant mice exposed to 2.5% Sevo at embryonic days 14.5 and 15.5 exhibited transient neuronal migration deficits, with 25% of neurons delayed in deeper cortical layers. However, these neurons migrated to the cortex by postnatal day 8. Neonatal mice exposed to 2.5% Sevo experienced a 10% reduction in dendritic spine density in adolescence, associated with impaired somatosensory function, as assessed by the Von Frey test. Remarkably, Dex pretreatment ameliorated these pathological and functional changes. Thus, foetal or neonatal Sevo exposure can delay neuronal migration and reduce dendritic spine density. Dex co-administration effectively mitigates these adverse outcomes, supporting its potential use in paediatric anaesthesia to protect developing brains. Graphical abstract

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Inverse Admittance Characteristics of Gastric Cancer Cells Measured by a Validated Dielectrophoretic Microfluidic Platform - Jia‑Jiun Tsai; Yun-Jung Tsai; Mei Yu Huang; Chun-Ping Jen; Shu-Hui Lin (Journal of Medical and Biological Engineering, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Influence of Pearl river plume and coastal upwelling on planktonic foraminiferal assemblages in the northern South China Sea - Rick J. Yang; Hui-Ling Lin; Tai-Chun Lin; Jay Lee; James T. Liu; Horng-Sheng Mii (Marine Environmental Research, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Entropy-stabilized multi-element 2D TMDs: Tunable electronics and enhanced thermal stability - Ching-Wei Chin; Chong-Chi Chi; Kai-Yuan Hsiao; Yi-Hsin Fang; Dun-Jie Jhan; Chun-Hui Lin; Ming-Pei Lu; Ming-Yen Lu (Chemical Engineering Journal, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Dimeric citrinins diversity revealed by the deep-sea-derived Penicillium citrinum W23 - Tai-Zong Wu; Zhi-Hui He; Cheng-You Lin; You Li; Zheng-Biao Zou; Chun-Lan Xie; Tian-Hua Zhong; Xian-Wen Yang (Phytochemistry, 2025)

Seismic design and performance evaluation of prestressed prefabricated frame with martensitic SMA buckling-restrained rods - Zhao-Hui Gong; Jin Zhang; Bin Zeng; Chun-Lin Wang (Soil Dynamics and Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of a new natural bromopyrrole alkaloid agenakasine, a biosynthetically related metabolite laughine, and norzooanemonin from a marine sponge Agelas nakamurai - Chung-Wei Fu; Atallah F. Ahmed; Lin Chiang; Shu-Fen Chiou; Hui-Chun Wang; Jyh-Horng Sheu (Phytochemistry Letters, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

eDNA-Based Evaluation of the Haplotypic Diversity of Orange-Spotted Grouper (Epinephelus coioides) in Stock Enhancement Areas of Wanshan Archipelago - Chun Hui Ai; Yi Long Lin; Ming Ze Chen; Jun Hong Xia (Marine Biotechnology, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Identification of a Major QTL Associated with Body Color on ChrLG3 in Tilapia by GWAS - Zong Xian Zhu; Yin Yi Yao; Yi Long Lin; Chun Hui Ai; Jun Hong Xia (Marine Biotechnology, 2025)

The calcined Mg-Al hydrotalcite for copper adsorption and passivation of copper-contaminated soil - Chun-Yan Cao; Ming-Hui Nie; Si-Lin Chen; Wen-Ling Long; Min Wang; Shuang Zhao; Xin Wan; Zhi-Guo Song (Process Safety and Environmental Protection, 2025)

Beneficial impact of MTGase-modified fish gelatin on collagen supplementation in rats: Insights from serum metabolomics and gut microbiota - Chun-Yan Peng; Ting Fang; Hao-Bin Lin; Ni Zhang; Zi-Zi Hu; Hai-tao Wang; Ming-Hui Su; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2025)

In search of nanofiltration membranes for efficient lithium extraction from carbonate-type salt lakes - Ren-Jie Fan; Chun-Xu Zhang; Fujun Xiong; Lin-Hui Niu; Xiang-Xuan Ruan; Xiaohu Wang; Zhen-Yuan Wang; Mei-Ling Liu; Shi-Peng Sun; Weihong Xing (Desalination, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Remediation of Pb-contaminated soils using thermally activated Mg-Al hydrotalcite - Chun-Yan Cao; Wen-Ling Long; Si-Lin Chen; Ming-Hui Nie; Min Wang; Shuang Zhao; Xin Wan (Journal of Soils and Sediments, 2025)

The Deep Space Radiation Probe: Development of a first lunar science payload for space environment studies and capacity building - Loren C. Chang; Wei-Yi Lin; Yi-Hsuan Chou; Jen-Siang Lin; Chieh Lung; I. Chen; Kai-Jie Hou; Glenn Franco Gacal; Yi-Chung Chiu; Yushun Wang; Hui-Hui Chou; Chi-Kuang Chao; et al. (Advances in Space Research, 2025)

Targeted and non-targeted metabolic analysis of chlorpromazine in grass carp as well as the in-silico and metabolomics toxicity assessment - Jinxia Dai; Sen Zhang; Hui Lin; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Journal of Hazardous Materials, 2025)

A Rare Patient of SEZ6L2 Antibody–Associated Cerebellar Ataxia - Chen-hui Cao; Wen-li Li; Yao Zhang; Ting Wei; Chun-lin Yang; Xiao-li Li; Bin Liu (The Cerebellum, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Concentration-dependent effect of norfloxacin on iron toxicity in the intestine of large yellow croaker Larimichthys crocea (Richardson, 1846) - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Bin Liu; Min-Hui Yu; Hui Zhang; Fei Li (Frontiers in Marine Science, 2025)
This study explores the effects of norfloxacin (NOR) on oxidative damage, iron (Fe) transport, energy metabolism, and immunotoxicity in the intestine of large yellow croaker under Fe stress. The fish were subjected to Fe (180 μg/L), low-dose NOR (1.8 μg/L, LNOR), high-dose NOR (180 μg/L, HNOR), Fe plus LNOR, and Fe plus HNOR for 60 days. These results demonstrated that Fe alone exposure increased malondialdehyde (MDA), protein carboxylation (PC), and mortality rate, and impaired intestinal tissue, which was related to the increment of Fe accumulation. Compared to Fe alone exposure, Fe plus LNOR exposure decreased MDA, PC, and mortality rate, and alleviated intestinal malformations by improving Fe transport, energy metabolism, anti-inflammatory response, and protein folding protective effect, and reducing pro-inflammatory response, indicating that LNOR had an antagonistic effect on Fe toxicity. Compared to Fe alone exposure, Fe plus HNOR exposure elevated MDA, PC, and mortality rate, and deteriorated intestinal malformations by inhibiting Fe excretion, energy metabolism, anti-inflammatory response, and protein folding protective effect, and enhancing pro-inflammatory response, indicating a synergetic effect between HNOR and Fe stress. These findings suggested that NOR had a dose-dependent effect on Fe-toxicity to large yellow croaker, which contributes to revealing the molecular mechanisms behind their interaction and its ecological implications.

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Selective precipitation of calcium phosphate, N-struvite, and K-struvite from raw seawater for resource recovery - Thi-Hanh Ha; Nicolaus N.N. Mahasti; Hiep-Quang Ha; Po-Lin Liao; Yao-Hui Huang; Ming-Chun Lu (Journal of Water Process Engineering, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Epigenetic Modifications as Novel Therapeutic Strategies of Cancer Chemoprevention by Phytochemicals - Hui-Hsia Hsieh; Min-Zhan Kuo; I-An Chen; Chien-Ju Lin; Victor Hsu; Wei-Chun HuangFu; Tien-Yuan Wu (Pharmaceutical Research, 2025)

The joint impact of PM2.5 constituents on the risk of cerebrovascular diseases hospitalization: A large community-based cohort study - Shirui Chen; Yuqin Zhang; Ziqiang Lin; Ruqing Liu; Lingling Zheng; Xiuyuan Chen; Shao Lin; Yanji Qu; Chun Hao; Hui Tang; Jing Wei; Wangjian Zhang; et al. (Environmental Research, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

ClinOleic Impairs ROS Production and Phagocytosis in M1 Macrophages Without Affecting M1 Differentiation - Yi-Sheng Tsai; Hsuan-Te Yeh; Ming-Shan Chen; Hui-Ju Chang; Wen-Chun Lin; Shew-Meei Sheu (Cell Biochemistry and Biophysics, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Photoelectric synaptic device based on Cu2ZnSnS4/ZnO heterojunction for non-volatile vision memory - Shuaifei Mao; Jiantong Ge; Lingling Zhang; Yannan Dai; Sheng Jiang; Yafei Chen; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2024)

Association among polydisperse aerodynamic size of bioaerosols, biodiversity and urbanization in kindergartens - Tzu-Hsien Lin; Ying-Hsiang Chou; Tzu-Yu Hsu; Chun-Hui Hung; Chane-Yu Lai (Chemosphere, 2024)

Deformation characteristics and stability analysis of lean clay under cyclic loading - Han-Lin Wang; Yue-Hui Sun; Ren-Peng Chen; Chun-Yin Peng; Askar Khasanov (Transportation Geotechnics, 2024)

Phellintremulins A-C, antinociceptive sesquiterpenoids from the medicinal fungus Phellinus tremulae - Chun Tian; Li-Tang Sun; Tian Jin; Lin-Lin Yuan; Wei-Fang Xu; Hui-Xiang Yang; Tao Feng; Ji-Kai Liu (Phytochemistry, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Differential effects of oxytetracycline on detoxification and antioxidant defense in the hepatopancreas and intestine of Chinese mitten crab under cadmium stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Bin Zhang; Hui Zhang; Zi-Ming Liu; Min-Hui Yu; Bing Hu (Science of The Total Environment, 2024)

A new acetophenone derivative from Rhododendron irroratum subsp. pogonostylum - Yong-Fu Lu; Si-Xuan Liu; Chun-Lin Guo; Si-Yang Dai; Yi-Hui Yang; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Synthesis and antifungal activity of 2,4-dihydroxy-5-methylphenyl ethanone derivatives against phytopathogenic fungi in vitro - Lin Jia; Cui-Ping Zhang; Yi Zhu; Chun-Yan Zhao; Zeng-Hui Han; Dong-Bao Hu; Wei Shi (Phytochemistry Letters, 2024)

Evaluate the effect of β-cyclodextrin on the sensory and physicochemical properties of bitter gourd extract during thermal processing - Cam Thi Hong Tran; Hui-Min David Wang; Le Thi Hong Anh; Chitsan Lin; Chun-Yung Huang; Chia-Hung Kuo (Food Chemistry, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Retail location modeling of supermarket chains in Taipei city - Pei-Chun Lin; T.C. Edwin Cheng; Chia-Hui Hsu (Applied Geography, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Neuroprotective Effects of Probiotic Lactobacillus reuteri GMNL-263 in the Hippocampus of Streptozotocin-Induced Diabetic Rats - Jing-Ying Lin; Bruce Chi-Kang Tsai; Hui-Chuan Kao; Chien-Yi Chiang; Yun-An Chen; William Shao-Tsu Chen; Tsung-Jung Ho; Chun-Hsu Yao; Wei-Wen Kuo; Chih-Yang Huang (Probiotics and Antimicrobial Proteins, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Kinetin inhibits hepatic stellate cell activation and induces apoptosis via interactions with the TGF-β1/Smad signaling pathway - Fu-chang Jin; Jing-jing Chen; Qiu-xian Xu; Ming-Hui Zhou; Yi Lin; Qi-wei Zhang; Chang-chun Zhang; Zhen-gang Zhang (Toxicology and Applied Pharmacology, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Dual-modal artificial synapse based on a lead-free halide Cu2AgBiI6 for image processing and information encryption - Shuaifei Mao; Mingqing Cui; Sheng Jiang; Pengfei Zhao; Jie Lao; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Jadranka Travas-sejdic; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Enhanced struvite (MgNH4PO4·6H2O) granulation and separation from synthetic wastewater using fluidized-bed crystallization (FBC) technology - Thi-Hanh Ha; Nicolaus N.N. Mahasti; Cai-Sheng Lin; Ming-Chun Lu; Yao-Hui Huang (Journal of Water Process Engineering, 2023)

Special issue: Health, it matters: responsible mission for landscape and ecological engineering - Chun-Yen Chang; Hui-Mei Chen; Bau-Show Lin (Landscape and Ecological Engineering, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Different cold tolerances among three strains of large yellow croaker: related to antioxidant defense and energy metabolism - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Hui Zhang; Yu-Cong Huang; Wei-Guang Zou (Fish Physiology and Biochemistry, 2023)

Targeting autophagy receptors OPTN and SQSTM1 as a novel therapeutic strategy for osteoporosis complicated with Alzheimer's disease - Ran Duan; Chun-Gu Hong; Meng-Lu Chen; Xin Wang; Zhi-Lin Pang; Hui Xie; Zheng-Zhao Liu (Chemico-Biological Interactions, 2023)

Salinibacterium sedimenticola sp. nov., Isolated from Tidal Flat Sediment - Chun-Yan Lu; Lei Dong; Shuai Li; Wen-Hui Lian; Zhi-Liang Lin; Zhuo-Huan Zheng; Lei Gao; Bao-Zhu Fang; Wen-Jun Li (Current Microbiology, 2023)

Colletotrichum species causing anthracnose disease on avocado fruit in Taiwan - Chao-Jung Wu; Miao-Chun Lin; Hui-Fang Ni (European Journal of Plant Pathology, 2023)

Residue screening and analysis of enrofloxacin and its metabolites in real aquatic products based on ultrahigh-performance liquid chromatography coupled with high resolution mass spectrometry - Jinxia Dai; Ye Wang; Hui Lin; Yanmin Sun; Yuning Pan; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Food Chemistry, 2023)

Determination of chlorpromazine and its metabolites in animal-derived foods using QuEChERS-based extraction, EMR-Lipid cleanup, and UHPLC-Q-Orbitrap MS analysis - Jinxia Dai; Hui Lin; Yuning Pan; Yanmin Sun; Ye Wang; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Food Chemistry, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Human platelet mitochondria improve the mitochondrial and cardiac function of donor heart - Zhi Jun Lin; Soomin Kim; Hui Xing Cui; Kyuboem Han; Hong Kyu Lee; Chun-Hyung Kim; Young Cheol Kang; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2023)

Transcriptome and DNA Methylation Responses in the Liver of Yellowfin Seabream Under Starvation Stress - Yi Long Lin; Zong Xian Zhu; Chun Hui Ai; Ying Ying Xiong; Tong De Liu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2023)

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway - Sheau-Chung Tang; Chun-Te Lu; Jiunn-Liang Ko; Cheng-Hui Lin; Yu-Ping Hsiao (Chemico-Biological Interactions, 2023)

Thermoregulation and subjective thermal perception of N95 respirator users: Influence of significant workloads - Yi-Chun Lin; Hui-Chen Wei; Chen-Peng Chen (Building and Environment, 2023)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Breast cancer incidence in a national cohort of female workers exposed to special health hazards in Taiwan: a retrospective case-cohort study of ~ 300,000 occupational records spanning 20 years - Yun-Shiuan Chuang; Chun-Ying Lee; Pei-Chen Lin; Chih-Hong Pan; Hui-Min Hsieh; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Experimental and theoretical analysis for the shear capacity of the square rebar reinforced concrete beams during the period of the Republic of China (1912–1949) - Chengwen Zhang; Qing Chun; Yijie Lin; Hui Jin; Yaohua Wang (European Journal of Environmental and Civil Engineering, 2022)

Plant secondary metabolite and temperature determine the prevalence of Arsenophonus endosymbionts in aphid populations - Chun‐Yan Chang; Xiao‐Wan Sun; Pan‐Pan Tian; Ning‐Hui Miao; Yu‐Lin Zhang; Xiang‐Dong Liu (Environmental Microbiology, 2022)
Summary Transmission rate and role in hosts contribute to the prevalence of an endosymbiont. However, factors affecting transmission and role of facultative endosymbionts are still not well understood. Here, we illustrated that host plants and environmental temperatures affected the transmission, relative abundance and role of Arsenophonus in the cotton aphid Aphis gossypii . The transmission rate of this endosymbiont from mother aphids to offspring was relatively lower. High temperatures impeded the transmission, and infection rates declined as aphids were exposed to 30°C. Contents of amino acids and secondary metabolites were remarkably different among host plants. Aphids feeding on zucchini leaves containing a higher titre of amino acids and lower secondary metabolites harboured a relatively lower abundance of Arsenophonus . Concentrations of an amino acid and a plant secondary metabolite, cucurbitacin B, in aphid diet were not associated with Arsenophonus abundance. However, gossypol, another plant secondary metabolite, was strongly related with the abundance. Arsenophonus imparted a fitness benefit to aphids, and the benefit was dependent on host plants and gossypol concentration. In sum, plant secondary metabolite and environmental temperature affect transmission, relative abundance and role of Arsenophonus , which determine the endosymbiont prevalence in aphid populations.

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

The optimal combination of Nile red identification, colony polymerase chain reaction, and gas chromatography detection methods in screening for polyhydroxyalkanoicate-producing bacteria - Hung-Che Chou; Chia-Hsin Chen; Hsiao-Kai Chu; Chun-Mei Huang; Hui-Jun Wang; Wei-Lin Tu; Gia-Luen Guo (Archives of Microbiology, 2022)

Development of novel polymorphic microsatellite markers for Picea brachytyla - Shuai-Peng Si; Chun-Jing Wang; Ji-Zhong Wan; Yu-Lin Qian; Chun-Hui Zhang (Molecular Biology Reports, 2022)

Seasonal Distributions of Methane in a Populous Urban Coastal Sea Area - Hsiao-Chun Tseng; Chia-Chia Lin; Hui-Juan Pan; Yokie Tai Yuh Han; Gwo-Ching Gong (Frontiers in Marine Science, 2022)
Methane (CH 4 ) is an important greenhouse gas, and its concentrations in aquatic areas are heavily influenced by anthropogenic activities, especially human-induced eutrophication, polluted river discharge and wastewater treatment plant (WWTP) effluents. Although coastal areas and estuaries contribute large amounts of global oceanic CH 4 emissions, the relative contributions of different sources have not been well determined. The Tamsui River located in northern Taiwan is an urban river flowing through populated cities and thus likely carries large amounts of contaminants, such as nutrients and organic matter to the estuary. In this study, we characterized the spatial distribution and seasonal variations in CH 4 in the Tamsui River estuary adjacent marine areas. The sea-to-air CH 4 fluxes were also estimated to quantify the strength of the study area as an atmospheric CH 4 source. Our results showed that CH 4 concentrations in coastal sea areas were influenced by WWTP effluents, sediment and freshwater inputs. Thus, river discharge and nutrient levels as well as strong vertical mixing and disturbances might increase CH 4 concentrations and emissions. The seasonal surface CH 4 concentrations and sea-to-air CH 4 fluxes were 13.7 ± 18.7 nM and 41.7 ± 68.0 μmol m -2 d -1 in autumn; 29.3 ± 19.8 nM and 61.3 ± 44.6 μmol m -2 d -1 in spring; 21.8 ± 13.9 nM and 37.0 ± 26.2 μmol m -2 d -1 in summer; and 27.0 ± 21.4 nM and 85.9 ± 75.4 μmol m -2 d -1 in winter.

Investigation on grouting diffusion in inclined fracture with flowing water conditions - Jia-fan Zhang; Xun-xun Chen; Yang Liu; Hui-mei Zhang; Chun-lin Wang; Gang Fang (Arabian Journal of Geosciences, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Sabulicella rubraurantiaca gen. nov., sp. nov., a new member of the family Acetobacteraceae, isolated from desert soil - Zhi-Liang Lin; Shuai Li; Qi-Chuang Wei; Wen-Hui Lian; Chun-Yan Lu; Lu Xu; Li-Nan Huang; Lei Dong; Wen-Jun Li (Archives of Microbiology, 2022)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Projections from Infralimbic Cortex to Paraventricular Thalamus Mediate Fear Extinction Retrieval - Yan Tao; Cheng-Yun Cai; Jia-Yun Xian; Xiao-Lin Kou; Yu-Hui Lin; Cheng Qin; Hai-Yin Wu; Lei Chang; Chun-Xia Luo; Dong-Ya Zhu (Neuroscience Bulletin, 2021)

Chronic Oral Administration of Magnesium-L-Threonate Prevents Oxaliplatin-Induced Memory and Emotional Deficits by Normalization of TNF-α/NF-κB Signaling in Rats - Xin Zhou; Zhuo Huang; Jun Zhang; Jia-Liang Chen; Pei-Wen Yao; Chun-Lin Mai; Jie-Zhen Mai; Hui Zhang; Xian-Guo Liu (Neuroscience Bulletin, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Mechanism of contractile dysfunction induced by serotonin in coronary artery in spontaneously hypertensive rats - Hao Wang; Xiao-Yan Gao; Fang Rao; Hui Yang; Zhao-Yu Wang; Lin Liu; Su-Juan Kuang; Qi Wu; Chun-Yu Deng; Jing-Song Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

Dynamic response and mechanical deformation properties of the soil cutting slope under train cyclic loads - Qiang Xie; Zhi-hui Wu; Chun-bo He; Jie Dong; Zhi-lin Cao; Li Liang (Arabian Journal of Geosciences, 2020)

The Arabidopsis kinase-associated protein phosphatase KAPP, interacting with protein kinases SnRK2.2/2.3/2.6, negatively regulates abscisic acid signaling - Kai Lu; Ya-Dong Zhang; Chun-Fang Zhao; Li-Hui Zhou; Qing-Yong Zhao; Tao Chen; Cai-Lin Wang (Plant Molecular Biology, 2020)

Development of a Direction-Oriented Motion and Short-Sitting and Lying Tai Chi (DOM-SSLTC) Model for Function Recovery in Stroke Patients - Lian-Hui Lee; Hwai-Ting Lin; Nai-Wen Tsai; Yung-Chieh Yen; Cheng-Hsien Lu; Chun-Chung Lui; Hsien-Ming Chung; Kun-Chang Tsai; Shih-Pin Hsu; Huan-Wen Tsui (Journal of Medical and Biological Engineering, 2019)

Research on the effect of coal seam inclination on gas migration channels at fully mechanized coal mining face - Pengxiang Zhao; Risheng Zhuo; Shugang Li; Chun-Hsing Ho; Haifei Lin; Hui Liu (Arabian Journal of Geosciences, 2019)

Characterization of the Cd(II) and nitrate removal by bacterium Acinetobacter sp. SZ28 under different electron donor conditions - Jun Feng Su; Chun Yu Gao; Ting Lin Huang; Xue Chen Bai; Dong Hui Liang; Lei He (Environmental Science and Pollution Research, 2019)

Transfer learning for predicting human skin sensitizers - Chun-Wei Tung; Yi-Hui Lin; Shan-Shan Wang (Archives of Toxicology, 2019)

Prediction of annual dengue incidence by hydro-climatic extremes for southern Taiwan - Hsiang-Yu Yuan; Tzai-Hung Wen; Yi-Hung Kung; Hsiao-Hui Tsou; Chun-Hong Chen; Li-Wei Chen; Pei-Sheng Lin (International Journal of Biometeorology, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Dopamine receptor D2 polymorphism is associated with alleviation of obesity after 8-year follow-up: a retrospective cohort study in obese Chinese children and adolescents - Jian-fang Zhu; Lian-hui Chen; Ke Yuan; Li Liang; Chun-lin Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Activating adenosine A1 receptor accelerates PC12 cell injury via ADORA1/PKC/KATP pathway after intermittent hypoxia exposure - Hong-Fang Mei; Neha Poonit; Yi-Chun Zhang; Chu-Yuan Ye; Hui-Lin Cai; Chen-Yi Yu; Yong-Hai Zhou; Bei-bei Wu; Jun Cai; Xiao-Hong Cai (Molecular and Cellular Biochemistry, 2018)

Identification of a new type tadalafil analogue in a supplement product - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Identifying crack initiation stress threshold in brittle rocks using axial strain stiffness characteristics - Mei-ben Gao; Tian-bin Li; Lu-bo Meng; Chun-chi Ma; Hui-lin Xing (Journal of Mountain Science, 2018)

Position-domain integrity risk-based ambiguity validation for the integer bootstrap estimator - Liang Li; Haodong Shi; Chun Jia; Jianhua Cheng; Hui Li; Lin Zhao (GPS Solutions, 2018)

Gracilibacillus eburneus sp.nov., a moderately halophilic bacterium isolated from Xinjiang province, China - Hui-Lin Guan; Yun-Jiao Zhang; Xiao-Ju Lu; Man Jia; Zheng-Yun Zhang; Xu-Hong Gao; Yong-Chun Ma; Fei Tian; Shu-Kun Tang (Archives of Microbiology, 2018)

Two new geranylphenylacetate glycosides from the barks of Cinnamomum cassia - Jun-Fen Zeng; Hu-Cheng Zhu; Jian-Wu Lu; Lin-Zhen Hu; Jin-Chun Song; Yong-Hui Zhang (Natural Product Research, 2017)

Morphology and controlling factors of the longitudinal profile of gullies in the Yuanmou dry-hot valley - Lin Ding; Fa-chao Qin; Hai-dong Fang; Hui Liu; Bin Zhang; Cheng-qiang Shu; Qing-chun Deng; Gang-cai Liu; Qian-qian Yang (Journal of Mountain Science, 2017)

Isolation and identification of a novel sildenafil analogue adulterant in herbal products - Ya-Tze Lin; Yen-Chun Huang; Hui-Chun Lee; Chen-Hsiang Liao; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2017)

Comparative Efficacy and Safety of Nine Anti-Platelet Therapies for Patients with Ischemic Stroke or Transient Ischemic Attack: a Mixed Treatment Comparisons - Hua-Pin Huang; Wan-Hui Lin; Sheng-Gen Chen; Li-Zhen Chen; Min-Yi Chen; Chun-Hui Che (Molecular Neurobiology, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Identification of a new sildenafil analogue adulterant, desethylcarbodenafil, in a herbal supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Ya-Tze Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Brittle Rock Modeling Approach and its Validation Using Excavation-Induced Micro-Seismicity - Chun-Chi Ma; Tian-Bin Li; Hui-Lin Xing; Hang Zhang; Min-Jie Wang; Tian-Yi Liu; Guo-Qing Chen; Zi-Quan Chen (Rock Mechanics and Rock Engineering, 2016)

Identification of a new tadalafil analogue, dipropylaminopretadalafil, in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2016)

QTL mapping of dehiscence length at the basal part of thecae related to heat tolerance of rice (Oryza sativa L.) - Ling Zhao; Chun-Fang Zhao; Li-Hui Zhou; Jing Lin; Qing-Yong Zhao; Zhen Zhu; Tao Chen; Shu Yao; Toshihiro Hasegawa; Tsutomu Matsui; Cai-Lin Wang (Euphytica, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Separation and identification of a novel tadalafil analogue adulterant in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Ying Li; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2015)

Hygromycin B-induced cell death is partly mediated by reactive oxygen species in rice (Oryza sativa L.) - Hui-Min Oung; Ke-Chun Lin; Tsung-Meng Wu; Nulu Naga Prafulla Chandrika; Chwan-Yang Hong (Plant Molecular Biology, 2015)

Impact of phloem girdling on water status in desert plants Alhagi sparsifolia Shap. (Fabaceae) and Karelinia Caspica (Pall.) Less. (Asteraceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zi-chun Guo; Chang-jun Li; Hui Guo; Fan-jiang Zeng (Brazilian Journal of Botany, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Sassarandainol: a new neolignan and anti-inflammatory constituents from the stem of Sassafras randaiense - Ya-Ling Hou; Hsun-Shuo Chang; Hui-Chun Wang; Sheng-Yang Wang; Tze-Ying Chen; Chu-Hung Lin; Ih-Sheng Chen (Natural Product Research, 2015)

TM-1-1DP exerts protective effect against myocardial ischemia reperfusion injury via AKT-eNOS pathway - Hui-Chun Ku; Shih-Yi Lee; Chi-Hsuan Chen; Yao-Hsing Wang; Chin-Ting Lin; Shoei-Sheng Lee; Ting-Hsuan Li; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Transcriptional regulation of the iac locus from Acinetobacter baumannii by the phytohormone indole-3-acetic acid - Hung-Yu Shu; Ling-Chun Lin; Tze-Kang Lin; Hao-Ping Chen; Hsueh-Hui Yang; Kou-Cheng Peng; Guang-Huey Lin (Antonie van Leeuwenhoek, 2015)

Inhibition of isoflavone biosynthesis enhanced T-DNA delivery in soybean by improving plant–Agrobacterium tumefaciens interaction - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Xiu-Lin Guo; Hui-Cong Li; Guo-Liang Li; Chun-Zhi Jiang; Meng-Chen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Characteristics of Na+ uptake in sugar beet (Beta vulgaris L.) seedlings under mild salt conditions - Guo-Qiang Wu; Qing-Zhao Shui; Chun-Mei Wang; Jin-Lin Zhang; Hui-Jun Yuan; Shan-Jia Li; Zuo-Jun Liu (Acta Physiologiae Plantarum, 2015)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

Association between the characteristics of metabolic syndrome and Alzheimer’s disease - Hui-Ting Yang; Yi-Jing Sheen; Chuen-Der Kao; Chin-An Chang; Ya-Chun Hu; Jiann-Liang Lin (Metabolic Brain Disease, 2013)

Relationship between road traffic noisescape and urban form in Hong Kong - Kin-Che Lam; Weichun Ma; Pak Kin Chan; Wing Chi Hui; King Lam Chung; Yi-tak Teresa Chung; Chun Yin Wong; Hui Lin (Environmental Monitoring and Assessment, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Isolation and characterization of lactic acid bacteria from pobuzihi (fermented cummingcordia), a traditional fermented food in Taiwan - Yi-sheng Chen; Hui-chung Wu; Chiung-mei Wang; Chia-chun Lin; Yi-ting Chen; Yu-jyun Jhong; Fujitoshi Yanagida (Folia Microbiologica, 2013)

Concurrent use of antiplatelets, anticoagulants, or digoxin with Chinese medications: a population-based cohort study - Hsin-Hui Tsai; Hsiang-Wen Lin; Chun-Ru Chien; Tsai-Chung Li (European Journal of Clinical Pharmacology, 2013)

Fhl1 as a downstream target of Wnt signaling to promote myogenesis of C2C12 cells - Jing-Yu Lee; I-Chun Chien; Win-Yu Lin; Shao-min Wu; Bo-Huei Wei; Yu-En Lee; Hu-Hui Lee (Molecular and Cellular Biochemistry, 2012)

The expression of a new HD-Zip II gene, MSHB1, involving the inhibitory effect of thidiazuron on somatic embryogenic competence in alfalfa (Medicago sativa L. cv. Jinnan) callus - Xin Hu; Chun-Rong Zhang; Hui Xie; Xia Huang; Yun-Feng Chen; Xue-Lin Huang (Acta Physiologiae Plantarum, 2012)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

Glycated hemoglobin A1c is superior to fasting plasma glucose as an independent risk factor for colorectal neoplasia - Yao-Chun Hsu; Han-Mo Chiu; Jyh-Ming Liou; Chun-Chao Chang; Jaw-Town Lin; Hui-Hsiung Liu; Ming-Shiang Wu (Cancer Causes & Control, 2012)

HepG2 cells infected with Klebsiella pneumoniae show DNA laddering at apoptotic and necrotic stages - Pei-Yin Yang; Wen-Xin Chen; Fong-Yin Chang; Hui-Wen Chen; Chun-Hung Lin; Yu-Chun Hsu; June Hsieh Wu (Apoptosis, 2012)

Overexpression of PGC-1β improves insulin sensitivity and mitochondrial function in 3T3-L1 adipocytes - Chun-Lin Gao; Guang-Ling Liu; Shi Liu; Xiao-Hui Chen; Chen-Bo Ji; Chun-Mei Zhang; Zheng-Kun Xia; Xi-rong Guo (Molecular and Cellular Biochemistry, 2011)

The effect of feed salinity on the biofouling dynamics of seawater desalination - Hui-Ling Yang; Jill R. Pan; Chihpin Huang; Justin Chun-Te Lin (Biofouling, 2011)

Loudness dependence of auditory evoked potentials (LDAEP) correlates with the availability of dopamine transporters and serotonin transporters in healthy volunteers—a two isotopes SPECT study - I Hui Lee; Yen Kuang Yang; Po See Chen; Hui Chun Huang; Tzung Lieh Yeh; Ru-Band Lu; Nan-Tsing Chiu; Wei Jen Yao; Shih-Hsien Lin (Psychopharmacology, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Variation of biomass and kinetic parameters for nitrifying species in the TNCU3 process at different aerobic hydraulic retention times - Tzu-Yi Pai; Ren-Jie Chiou; Chwen-Jeng Tzeng; Tung-Sheng Lin; Shan-Chun Yeh; Pao-Jui Sung; Chu-Hui Tseng; Chia-Ho Tsai; Yao-Sheng Tsai; Wen-Jui Hsu; Yuh-Ling Wei (World Journal of Microbiology and Biotechnology, 2010)

Factors impacting on the excess arseniasis prevalence due to indoor combustion of high arsenic coal in a hyperendemic village - Guo-Fang Lin; Hong Meng; Hui Du; Hong-Chao Lu; Yun-Shu Zhou; Ji-Gang Chen; Klaus Golka; Jia-Chun Lu; Jian-Hua Shen (International Archives of Occupational and Environmental Health, 2010)

Increasing trend of the incidence of esophageal squamous cell carcinoma, but not adenocarcinoma, in Taiwan - Ching-Liang Lu; Hui-Chu Lang; Jiing-Chyuan Luo; Chun-Chu Liu; Han-Chieh Lin; Full-Young Chang; Shou-Dong Lee (Cancer Causes & Control, 2010)

Effect of PARP-1 deficiency on DNA damage and repair in human bronchial epithelial cells exposed to Benzo(a)pyrene - Gong-hua Tao; Lin-qing Yang; Chun-mei Gong; Hai-yan Huang; Jian-dong Liu; Jian-jun Liu; Jian-hui Yuan; Wen Chen; Zhi-xiong Zhuang (Molecular Biology Reports, 2009)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

Naringenin-Loaded Nanoparticles Improve the Physicochemical Properties and the Hepatoprotective Effects of Naringenin in Orally-Administered Rats with CCl4-Induced Acute Liver Failure - Feng-Lin Yen; Tzu-Hui Wu; Liang-Tzung Lin; Thau-Ming Cham; Chun-Ching Lin (Pharmaceutical Research, 2009)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Functional differentiation in the anterior gills of the aquatic air-breathing fish, Trichogaster leeri - Chun-Yen Huang; Wen Lee; Hui-Chen Lin (Journal of Comparative Physiology B, 2008)

Applying the grey assessment to the evaluation system of ecological green space on greening projects in Taiwan - Li-Wei Lin; Chui-Hui Chen; Hsueh-Cherng Chang; Tzu-Chun Chen (Environmental Monitoring and Assessment, 2007)

Genetic analysis of an attenuated Papaya ringspot virus strain applied for cross-protection - Chu-Hui Chiang; Chun-Yee Lee; Ching-Hsien Wang; Fuh-Jyh Jan; Shih-Shun Lin; Tsung-Chi Chen; Joseph A. J. Raja; Shyi-Dong Yeh (European Journal of Plant Pathology, 2007)

Status of Biological Studies and Aquaculture Development of the Mud Crab, Scylla serrata, in China: An Experimental Ecological Studies - Wang Gui-zhong; Li Shao-jing; Zeng Chao-shu; Lin Shu-jun; Kong Xiang-hui; Ai Chun-xiang; Lin Qiong-wu (Aquaculture International, 2005)

Site-Directed Mutagenesis of the Conserved Threonine, Tryptophan, and Lysine Residues in the Starch-Binding Domain of Bacillus sp. Strain TS-23 a-Amylase - Huei-Fen Lo; Wen-Ying Chiang; Meng-Chun Chi; Hui-Yu Hu; Long-Liu Lin (Current Microbiology, 2004)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Establishment of red fluorescent protein-tagged HeLa tumor metastasis models: Determination of DsRed2 insertion effects and comparison of metastatic patterns after subcutaneous, intraperitoneal, or intravenous injection - Jau-Yeong Lu; Hui-Chun Chen; Ricky Yuan-Yuan Chu; Tsu-Chun Emma Lin; Ping-I Hsu; Ming-Shyan Huang; Ching-Jiunn Tseng; Michael Hsiao (Clinical & Experimental Metastasis, 2003)

Wogonin and fisetin induction of apoptosis through activation of caspase 3 cascade and alternative expression of p21 protein in hepatocellular carcinoma cells SK-HEP-1 - Yen-Chou Chen; Shing-Chuan Shen; Woan-Rouh Lee; Hui-Yi Lin; Ching-Huai Ko; Chun-Ming Shih; Ling-Ling Yang (Archives of Toxicology, 2002)

Stopped-flow kinetic study of the peroxidase reactions of mangano-microperoxidase-8 - Hui-Chun Yeh; Chia-Huei Yu; Jinn-Shyan Wang; Suei-Tein Chen; Oliver Y. Su; Wann-Yin Lin (JBIC Journal of Biological Inorganic Chemistry, 2002)

Stopped-flow kinetic study of the H2O2 oxidation of substrates catalyzed by microperoxidase-8 - Hui-Chun Yeh; Jinn-Shyan Wang; Oliver Y. Su; Wann-Yin Lin (JBIC Journal of Biological Inorganic Chemistry, 2001)